The aviator [videorecording (DVD)] - DiCaprio, Leonardo; Blanchett, Cate, 1969-; Beckinsale, Kate; Reilly, John C., 1965-; Baldwin, Alec, 1958-; Alda, Alan, 1936-; Holm, Ian, 1931-2020; Huston, Danny, 1962-; Stefani, Gwen, 1969-; Law, Jude, 1972-; Scott, Adam, 1973-; Ross, Matt; et al. (Warner Home Video, 2005)
Howard Hughes was a rich young man from Texas, heir to his father's fortune, when he decided he wanted to make movies. Age 21, he made the most expensive Hollywood film ever (at the time); and went on to break air-speed records, make another fortune in aircraft design, smash Charles Lindbergh's round-the-world flight record, and be romantically linked with almost all of Hollywood's famous beauties. Nevertheless, he died alone, sealed into a room he never left, the victim of compulsions that drove him to greatness, while containing the seeds of his undoing.